The Global Contemporary and the Rise of New Art Worlds - Belting, Hans; Buddensieg, Andrea; Weibel, Peter (ZKM | Center for Art and Media Karlsruhe; MIT Press, 2013)
Mapping the new geography of the visual arts, from the explosion of biennials to the emerging art markets in Asia and the Middle East. The geography of the visual arts changed with the end of the Cold War. Contemporary art was no longer defined, exhibited, interpreted, and acquired according to a blueprint drawn up in New York, London, Paris, or Berlin. The art world distributed itself into art worlds. With the emergence of new art scenes in Asia and the Middle East and the explosion of biennials, the visual arts have become globalized as surely as the world economy has. This book offers a new map of contemporary art's new worlds. The Global Contemporary and the Rise of New Art Worlds documents the globalization of the visual arts and the rise of the contemporary over the last twenty years. Lavishly illustrated, with color throughout, it tracks developments ranging from exhibition histories and the rise of new art spaces to art's branding in such emerging markets as Hong Kong and the Gulf States. Essays treat such subjects as curating after the global turn; art and the migration of pictures; the end of the canon; and new strategies of representation.
English; Arabic
Keywords: 20th century; Art exhibitions; Biennials; N61-72 Theory. Philosophy. Aesthetics of the visual arts; Global